Evaluasi Kebutuhan Air Bersih Untuk Masyarakat di Kecamatan Binjai Timur - Muhammad Mufti Farabi; Mahliza Nasution; Nuril Mahda Rangkuti (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2022)
Binjai is a city in North Sumatra. Along with the increase in population and the increase in industrial zones every year, automatically the need for the use of clean water continues to grow. In East Binjai Subdistrict, the existence of Drinking Water Service Providers is far from satisfactory. This happens because many residents still use groundwater sources (dug wells) as one of the main sources of residents to obtain clean water. By thinking about these problems, the author wants to evaluate the need for clean water in East Binjai District until 2027 and the number of clean water service coverage in East Binjai District in 2027. Based on the results of research that has been carried out, the need for clean water based on the total population of East Binjai District in 2027 is 109,612 lt/s, while clean water needs are based on the number of customers of East Binjai District in 2027 of 18,018 lt/s. As for the service coverage of Company M in 2027, it was obtained by 17.946%, with the description of 66,227 people in the total population of East Binjai District, the number of people who use Company M's services for daily use is only 11,326 people. The remaining 54,342 people still use independent methods to obtain clean water.